Brachial thoracic bullet wound with damage to the left atrium - A. V. Slobodyanik; D. A. Yasuchenya; V. N. Kravchuk; I. I. Dzidzava; B. N. Kotiv (Вестник хирургии имени И.И. Грекова)
Bullet wounds to the heart on the battlefield are quite rare. The victims usually die in the near future after being in[1]jured. The injuring agent most often pierces through the heart, thereby causing massive bleeding and cardiac arrest. All rare, unique cases when the wounded remained alive are associated either with the loss of kinetic energy of the injuring agent when the defeat occurs at the limit of flight range, or with a «behind the barrier» defeat when a bullet or fragment initially penetrates the «barrier» (armor, vehicle, ricochet from weapons or other solid objects, etc.). Injuries, when a bullet hits the shoulder, ricochets off the bones of the skeleton or spine and hits the heart, are found in isolated cases.In the presented clinical observation, the combatant was wounded in the left shoulder. At the stages of medical evacuation, a chest injury with heart damage and the presence of a foreign body was revealed. Initially, the wound proceeded without hemodynamic disorders, and only 36 hours after the injury, the first symptoms of a violation of the cardiovascular system appeared. As a matter of urgency, the wounded man was transferred by the intensive care team to a specialized cardiac surgery department, where emergency surgery was performed in conditions of artificial circulation. The postoperative period was smooth. The victim is currently receiving rehabilitation treatment. Heart injuries in combat conditions are highly relevant and are an extremely serious problem of the medical service at all stages of evacuation, diagnosis and treatment. The difficulties in diagnosing heart wounds are associated with the lack of the necessary hardware and diagnostic base near the line of contact and the extremely rapid development of the terminal condition. High mortality rates are due to acute cardiac disorders (cardiac tamponade, damage to the coronary arteries, massive bleeding). Subjective signs of cardiac injuries are often absent due to the admission of such a category of patients in an unconscious state. In this clinical case, timely diagnosis at the stages of medical care and interdisciplinary interaction made it possible to urgently refer a victim with a brachiothoracic bullet wound to the stage of specialized care.